FISH MEASURING BOARD FOR RACIAL INVESTIGATIONS - Noble, A (Indian Journal of Fisheries, 2011)
To measure the linear dimensions other than the total length of a fish for racial investigations, a board is designed and got fabricated. It has a mirror base and a half metre scale. There is a grooved wheel and two pulleys at its back, carrying a steel tape with a needle wire fixed at its zero. When the wheel is rotated the tape runs from left to right and the needle rides over the fish on the board. The tape gives the measurement and the rider helps to pin-point it avoiding parallax error. The board is waterproof, inexpensive and easy to make.